Negative prognostic significance of primary cilia, CD8+ tumor infiltrating lymphocytes and PD1+ cells expression in clear cell renal cancer - Rozsypalova, Aneta; Rosova, Blanka; Filipova, Alzbeta; Nikolov, Dimitar Hadzi; Chloupkova, Renata; Richter, Igor; Proks, Jan; Zachoval, Roman; Matej, Radoslav; Melichar, Bohuslav; Buchler, Tomas; Dvorak, Josef (Journal of Balkan Union of Oncology, 2019)
PURPOSE: The aim of this study was to investigate the potential association and combined prognostic significance of the frequency of primary cilia (PC), programmed cell death protein-1 receptor (PD1) and CD8+ tumor infiltrating lymphocytes (TIL) in patients with clear cell renal cancer (ccRCC). METHODS: The frequency of PC, PD1 expression and the frequency of intratumoral CD8+ TIL were evaluated in 104 ccRCC patients. RESULTS: The median frequency of PC was 0.003. The expression of PD1+ cells were <5% in 52 patients, 5-25% in 34 patients and 26-50% in 13 patients and >50% in 5 patients. Intratumoral CD8+ TIL were evaluable in all patients: negative in 1 patient, <25% in 63, 26-50% in 29 and >50% in 11 patients. Overall survival (OS) according to the frequency of PC was significantly shorter in patients with higher frequency (≥0.002) than in patients with lower frequency (<0.002) (p<0.001). Median OS was significantly shorter in patients with higher (25%) CD8+ TIL and higher (>25%) PD1+ expression than in patients with lower (<25%) expression (4.6 vs. 97. years, p=0.006 and 2.9 vs. 8.9 years, p=0.006, respectively). CONCLUSIONS: The present study provides the first data on the potential association and combined prognostic significance of frequency of PC, PD1+ cells and CD8+ TIL in patients with clear cell renal cancer.
Keywords: senioři; Carcinoma, Renal Cell; Cilia; senioři nad 80 let; Prognosis; regulace genové exprese u nádorů; antigeny CD279; Kaplan-Meier Estimate; Lymphocytes, Tumor-Infiltrating; tumor infiltrující lymfocyty; Middle Aged; mužské pohlaví; Kaplanův-Meierův odhad; karcinom z renálních buněk; Adult; Programmed Cell Death 1 Receptor; cilie; Aged, 80 and over; CD8-pozitivní T-lymfocyty; Disease-Free Survival; ženské pohlaví; prognóza; Humans; Gene Expression Regulation, Neoplastic; lidé středního věku; dospělí; CD8-Positive T-Lymphocytes; Aged; Female; přežití bez známek nemoci; lidé; Male